The Effect of Asset Structure, Sales Growth, Return on Equity, and Current Ratio on Capital Structure in Energy Sector Companies Listed on the Indonesia Stock Exchange - Siska Nur; Fuad Ramdhan Ryanto (JURNAL ECONOMINA, 2026)
This study aims to analyze the effects of Asset Structure, Sales Growth, Return on Equity, and Current Ratio on Capital Structure in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2022 period. This research employed a quantitative approach with an associative research design. The data used were secondary data obtained from the financial statements of energy sector companies. The population consisted of 75 companies, while 68 companies were selected as the research sample using purposive sampling. Data were analyzed using multiple linear regression after the classical assumption tests were conducted. The results show that Asset Structure, Sales Growth, and Current Ratio have a positive and significant effect on Capital Structure. Meanwhile, Return on Equity does not have a significant effect on Capital Structure. Simultaneously, Asset Structure, Sales Growth, Return on Equity, and Current Ratio have a significant effect on Capital Structure. The coefficient of determination indicates that the independent variables explain 15.5% of the variation in Capital Structure, while the remaining 84.5% is influenced by other factors outside the research model. These findings imply that asset composition, sales growth, and liquidity are important considerations in determining the capital structure of energy sector companies. This study contributes empirical evidence on the determinants of capital structure in the Indonesian energy sector.